Community Contribution to Ecosystem Restoration in Giri Mulyo Village as a Role Model of Kerinci Seblat National Park, Jambi-Sumatra, Indonesia. Issue 1 (January 2022) - Hariyadi, A R S; Puroso, P; Ismail, T; Nurhamidi,; Mirza, E; Kaemal,; Indrawan,
Abstract: Kerinci Seblat National Park (KSNP) experienced deforestation due to agriculture and plantation activities conducted by people residing around the national park. A role model concept was taken to address this problem, and to restore the forest by involving local communities in Giri Mulyo Village. The objective is to assess a model for ecological restoration and socio-economic support. Indicators include livelihood replacement, and tree species consisting endemic and multi-purpose (MPTS) biodiversity measured using biodiversity indices. Analysis of the species composition in the restored area shows Margalef species richness in the low category (0.88) but the Shannon diversity index (H'=1.72) and Evenness (E=0.61) suggest moderate diversity. The Simpson's dominance index of 0.77 (away from 0) indicates that the site in Giri Mulyo Village is not dominated by a few tree species. These indices demonstrate biodiversity improvement compared to monoculture practices. This approach is a novel way to simultaneously resolve conflict and encroachment issues. Ideal scenario requires that MPTS commodities planted at a composition of at least 50% of the total tree density to support livelihoods. An alternative income source is still needed to compensate for the decreased agricultural income due to the restoration until MPTS can be harvested.